precalculus

Find the difference quotient by using
f(x+h)−f(x)/h


1) f(x) = √(2x+1)
answer

(√(2x+1+2h) - √(2x+1))/h

can you check please

asked by jack
  1. correct so far

    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Find an equation of the line that bisects the obtuse angles formed by the lines with equations 3x-y=1 and x+y=-2. a. (3√2 +√10)x-(√10 + √2)y-2√10+√2=0 b. (3√2 - √10)x+(√10 -
  2. 8th grade algebra

    Can you check my answers? 1. 3√20/√4 = 3√(5)(4)/2 = 3(2)√5/2 = 3√5 2. 4√15/√9 = 4√15/3 3. √12/√16 = √4(3)/4 = 2√3/4 = √3/2 4. √10/√5 =
  3. Algebra - Check My Work

    For Question 1-8 Simplify the Radical Expression *** - My Answer 1.√45 3√5*** 2.√180x^2 6x√5*** 3.√150x^3 k^4 5xk^2√6x*** 4.√21y * 5√49y 35y√21*** 5.(The square root sign
  4. Algebra

    1. Simplify the expression: 4√18+5√32 A.45√2 B.32√2 C.116√2 D.9√50 2. Simplify the expression: 7√5-3√80 A.-5√5 B.-4√75 C.-5 D.4√-75 3. Simplify the expression:
  5. Algebra 1

    Simplifying Radicals, Use the quotient property to simplify the expression. 3 times the square root of 6/3 3*sqrt(6/3) is the same thing as saying 3*sqrt(2) Your problem: 3√(6/3) is the same as 3√6/√3 To
  6. Algebra 2 Answer Check

    Simplify by rationalizing each denominator. 1. 2/√3 A: 2√3 / 3 2. -18/√6 A: -3√6 Add or subtract. 3. 4√3 - 9√3 A: -5√3 4. √8 - 15√2 A: -13√2 5. √45 + √20 A:
  7. Algebra

    How would i complete these problems? 1. (√6mn)^5 2. ^3√16x - ^3√2x^4 3.^4√x • ^3√2x 4. ^3√72x^8 5. √63a^5b • √27a^6b^4 and are these problems correct? 6. √2025xy/3√3
  8. Algebra

    Simplify the expressions and solve the equations 1. 2√3 - √12 My answer: 2√3 - 2√3 = 0 2. √(5p + 5)^2 = √(6p + )^2 I got the answer p = 4 3. √(28) + √(63) + √(175) This one
  9. Math

    I need someone to check my homework answers. I don't really know this stuff but i'm trying to do better in math this year. I didn't understand how to do some either. 1. √12 I got 2√3 2. √9a^3 I got 3a 3. √8
  10. Algebra Work Check

    1. 5√6 * 1/6√216 5/6 * √1296 5/6 * √144 * √9 = 30 2. -9√28a^2 * 1/3√63a -3√1764a^3 -3√49a^2 * √36a -3*7a*6√a = -126a√a

More Similar Questions